A contemplação mística do um em Plotino - Brandão, Bernardo Guadalupe S. L. (2010)
Resumo  Uma das características mais importantes do pensamento de Plotino são suas descrições da contemplação do Um, o princípio supremo da realidade. Essa contemplação é uma experiência mística, não porque é um tipo de estado irracional, mas por sua natureza supra-racional. Neste artigo, tento resumir a visão plotiniana dessa experiência, discutindo suas particularidades.   Abstract   One of the most interesting features of Plotinus` thought is his descriptions of the contemplation of the One, the supreme principle of reality. This contemplation is a mystic experience, not because it is a kind of irrational state, but for his supra-rational nature. In this paper, I try to summarize the plotinian view of this experience, discussing its particularities.   Keywords: neoplatonism; mystics; Plotinus